2010
DOI: 10.1111/j.1365-246x.1971.tb03384.x
|View full text |Cite
|
Sign up to set email alerts
|

Earth Motion Caused by Local Atmospheric Pressure Changes

Abstract: Observations have been made of the local atmospheric pressure field and the long-period seismic noise fields both on the surface of the Earth and in a mine at a depth of 183 metres. The observations show that during windy intervals and in the period range 20-100 s there is a strong correlation between local atmospheric pressure changes and the noise recorded by a vertical seismograph located on the surface. In contrast, over the same range of periods there is no correlation between the seismic noise recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Lognonné et al (1996) have shown that, even on Earth, prototype Martian seismometers can reach low noise levels at a quiet site, when protected by a windshield, leaving the overall ground deformation as the ultimate and unescapable noise on a planet with a windy atmosphere. This has been welldocumented on Earth, at LPs (Sorrells, 1971;Sorrells et al, 1971) and at SPs of varying durations (Criswell et al, 1975;Steeples et al, 1997;Withers et al, 1996). Wind-generated microseismic noise on Mars has been estimated by Lognonné and Mosser (1993) and later modeled with Large Eddies Simulations by Lognonné et al (2012), while temperaturegenerated noise was estimated by van Hoolst et al (2003).…”
Section: Martian Seismic Noisementioning
confidence: 86%
“…Lognonné et al (1996) have shown that, even on Earth, prototype Martian seismometers can reach low noise levels at a quiet site, when protected by a windshield, leaving the overall ground deformation as the ultimate and unescapable noise on a planet with a windy atmosphere. This has been welldocumented on Earth, at LPs (Sorrells, 1971;Sorrells et al, 1971) and at SPs of varying durations (Criswell et al, 1975;Steeples et al, 1997;Withers et al, 1996). Wind-generated microseismic noise on Mars has been estimated by Lognonné and Mosser (1993) and later modeled with Large Eddies Simulations by Lognonné et al (2012), while temperaturegenerated noise was estimated by van Hoolst et al (2003).…”
Section: Martian Seismic Noisementioning
confidence: 86%
“…It can detect the local winds that create turbulence and Reynold stresses on the WTS and SEIS. In addition, the wind moves the InSight lander and tether (Murdock et al 2016, this issue) and creates micro-seismic noise from short period surface waves trapped in low velocity surface « SPAC 11214 layout: Small Condensed v.2.1 file: spac321.tex (ELE) class: spr-small-v1.2 v.2016/06/09 Prn:2016/12/02; 14:37 p. 12/91» « d o c t o p i c : R e v i e w P a p e rn u m b e r i n g s t y l e : C o n t e n t O n l yr e f e r e n c e s t y l e : a p s » layers (Withers et al 1996) as well as the effect of the atmospheric movement coupling to the surface over a broader region (Sorrells et al 1971). Although no formal wind related engineering requirements were developed during the landing site selection process, the sensitivity of both the landing system and SEIS to the winds influenced the selection.…”
Section: Windsmentioning
confidence: 99%
“…Correction due to this effect is usually added to the aforementioned formula in the analyses (Crossley et al, 1995;Merriam, 1992;Niebauer, 1998;Spratt, 1982;Van Dam and Wahr, 1987;Warburton and Goodkind, 1977). This effect is not negligible and in fact was claimed to be larger than the previously mentioned effect in earlier period of seismic noise study (Sorrells, 1971;Sorrells et al, 1971). But it is smaller than the right-hand side of the aforementioned formula.…”
Section: Causementioning
confidence: 89%